2013
DOI: 10.1016/j.febslet.2013.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibition enhances resistance to DNA damage via upregulation of Rpn4‐dependent DNA repair genes

Abstract: Edited by Ivan SadowskiKeywords: Yeast DNA damage response Proteasome Rpn4 RAD52 a b s t r a c t The 26S proteasome is an ATP-dependent multi-subunit protease complex and the major regulator of intracellular protein turnover and quality control. However, its role in the DNA damage response is controversial. We addressed this question in yeast by disrupting the transcriptional regulation of the PRE1 proteasomal gene. The mutant strain has decreased proteasome activity and is hyper-resistant to various DNA-damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 45 publications
4
32
0
Order By: Relevance
“…The transcription factor Rpn4 of S. cerevisiae is involved in regulation of DNA repair (17,18) and functions as a transcriptional activator of 26S proteasomal subunits (13,19) a All the strains were grown in TM-G for 16 h, followed by 4 h in MM-X. Differentially expressed genes in the ΔflbA and Δfum21 strains can be found in references 9 and 10. b When no function of the gene could be inferred from MycoCosm, GO/KEGG terms, and a blastp search, the functional annotation is given as "no annotation."…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor Rpn4 of S. cerevisiae is involved in regulation of DNA repair (17,18) and functions as a transcriptional activator of 26S proteasomal subunits (13,19) a All the strains were grown in TM-G for 16 h, followed by 4 h in MM-X. Differentially expressed genes in the ΔflbA and Δfum21 strains can be found in references 9 and 10. b When no function of the gene could be inferred from MycoCosm, GO/KEGG terms, and a blastp search, the functional annotation is given as "no annotation."…”
Section: Discussionmentioning
confidence: 99%
“…Msn2 and Msn4 are the key regulators of the general stress response, while Yap1 is involved in the oxidative stress response and also in specific cases of drug resistance, and Sfp1 is involved in ribosome biogenesis and, indirectly, in resistance to many stress conditions. The regulatory associations involving Rpn4, a transcription factor that controls proteosomal genes and that is implicated in the oxidative stress response and DNA repair (Jelinsky et al, 2000; Karpov et al, 2013), in particular induced by the genotoxic agent MMS (Spasskaya et al, 2014), are also of interest. Rpn4 has been shown to regulate 43% of all DHA1/DAG genes, including the 4 genes ( ARN1 , ATR1 , AQR1 , and FLR1 ) whose expression and/or localization was found to change in response to MMS treatment leading to replicative stress (Tkach et al, 2012).…”
Section: Clues On the Functional Analysis Of Dha1/dag Transporters Bamentioning
confidence: 99%
“…It was reported that inhibition of proteasome activity impairs DNA repair and DNA damage-induced apoptosis in cancer cells [7]. Other studies demonstrated that proteasome plays rather a negative role in DDR [8]. Evidence suggested that proteasome might regulate DDR either indirectly via availability of ubiquitin pool or directly by deubiquitinating and degrading DDR proteins.…”
Section: Introductionmentioning
confidence: 99%